The Estrogen Receptor Joins Other Cancer Biomarkers as a Predictor of Outcome - Kimberly K. Leslie; Kristina W. Thiel; Henry D. Reyes; Shujie Yang; Yuping Zhang; Matthew J. Carlson; Nirmala S. Kumar; Donghai D. Dai (Obstetrics and Gynecology International)
Endometrial cancer, the most common gynecologic malignancy in the United States, is on the rise, and survival is worse today than 40 years ago. In order to improve the outcomes, better biomarkers that direct the choice of therapy are urgently needed. In this review, we explore the estrogen receptor as the most studied biomarker and the best predictor for response for endometrial cancer reported to date.